DIGITAL FORENSIC ANALYSIS OF SYSTEM ACCESS ACTIVITY USING SERVER LOGS - Avram Fadhilah; Hendra Gunawan (RADJA PUBLIKA, 2026)
This study examines how server log data can be utilized as digital evidence through a structured forensic analysis approach. The proposed framework integrates multiple log sources, including authentication, system, application, and network logs, to reconstruct system access activities. The proposed method applies rule-based correlation and statistical thresholding to detect anomalies across multi-source logs. Experimental results based on 247,318 log entries indicate that the proposed approach achieves a detection rate of 94.7% with a false positive rate of 3.2%. The analysis identifies multiple categories of security threats, including brute force attacks, privilege escalation, data exfiltration, and forensic trace obfuscation.